(untitled) (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2022)
Adolescence is a period of transition from childhood to adulthood. The adolescent phase is the identity search stage. They often try a lot of things. When they fall into the wrong environment and they will be trapped in promiscuity. Promiscuity is a form of deviant social interaction, crossing moral boundaries, rules and feelings of shame. This community service activity provides socialization about the dangers of promiscuity in adolescents in Ngogri village, Megaluh sub-district, Jombang district. The purpose of the activity is to open up insight for teenagers about the negative impact of promiscuity and how to prevent it. The results of the implementation of community service activities, teenagers begin to open their insights and knowledge about the dangers of promiscuity and are able to implement a healthy life and improve their spirituality. Keywords: Adolescence, promiscuity